The Effect Of Training On Personnel Performance At UPT. Dairi Regency Fire Brigade - Amudi Parulian Situmeang; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the effect of training on personnel performance at UPT. Dairi Regency Fire Department. This research was conducted with a causal associative quantitative approach. The sample used was all employees with a total of 83 people taken by prposive sampling Based on the results of data analysis, this study found that training had a positive and significant influence on personnel performance. The results of the hypothesis test showed a t-count value of 13.526, which is greater than the t-table 1.67109, with a significance value of 0.000 which is smaller than 0.05. The regression coefficient shows that each unit increase in training will lead to an increase in personnel performance by 0.899 units, assuming other variables are considered fixed. In addition, the results of the determination test showed that training could explain 80% of the variability in personnel performance, which showed that the influence of training on personnel performance was very high. The remaining 20% is influenced by other factors that have not been studied. Thus, training has proven to have a positive and significant effect on improving personnel performance at UPT. Dairi Regency Fire Department.